2010
DOI: 10.1021/jf102005z
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and Its Oligomers from Wine Grapes Are Selective 1O2 Quenchers: Mechanistic Implication by High-Performance Liquid Chromatography−Electrospray Ionization−Tandem Mass Spectrometry and Theoretical Calculation

Abstract: Resveratrol and its oligomers, abundantly present in wine grapes, are believed to be effective phytoalexins for the phenomenon "French paradox" partially by virtue of their powerful antiradical properties. EPR spin-trapping technique was utilized, demonstrating all polyphenols were selective (1)O2 quenchers but not effective (•)OH and O2(•¯) scavengers. On the basis of the HPLC-ESI-MS(2) analysis for the simulated reactions of polyphenols with (1)O2, the molecular weights of the resulting photochemical product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 44 publications
0
14
2
Order By: Relevance
“…ε-viniferin, Fig. 7) were also identified in grapevine leaves and wine by-products (Jiang et al, 2010;Lima et al, 1999;Moreno-Labanda et al, 2004;Pezet et al, 2003;Püssa et al, 2006;Vitrac et al, 2005).…”
Section: Stilbenesmentioning
confidence: 99%
“…ε-viniferin, Fig. 7) were also identified in grapevine leaves and wine by-products (Jiang et al, 2010;Lima et al, 1999;Moreno-Labanda et al, 2004;Pezet et al, 2003;Püssa et al, 2006;Vitrac et al, 2005).…”
Section: Stilbenesmentioning
confidence: 99%
“…Fig. 7 comprises stilbenes that have recently been identified in both grapes and wine: piceid, piceatannol glucoside (usually named astringin), pterostilbene, pallidol, parthenocissin and ameurensin G (Jiang, He, Jiang, Sun, & Pan, 2010). Oligomeric forms of the oxidation products of resveratrol-viniferins (e.g.…”
Section: Stilbenesmentioning
confidence: 99%
“…According to their work, the characteristic structure in the process of resveratrol quenching 1 O 2 is the carbon-carbon double bond. However, Jiang et al (2010) reported that resveratrol quinone ( 1-2 ) was the main product responsible for quenching 1 O 2 and suggested that what really matters in the mechanism is the resorcinol moiety [20]. In addition, according to our previous result [22], the carbon-carbon double bond and resorcinol moiety both were verified to be participants in the quenching reaction.…”
Section: Resultsmentioning
confidence: 95%
“…In the further investigation of the activity of stilbenes quenching 1 O 2 , many works so far have focused on its mechanism. Some hold the view that resorcinol ring could be oxidized to quinone when resveratrol quenches 1 O 2 [20]. Others propose that the mechanism of resveratrol 1 O 2 quenching is mainly because of the carbon-carbon double bond based on nuclear magnetic resonance (NMR) data [21].…”
Section: Introductionmentioning
confidence: 99%